The effects of employee participation in creative-relevant process and creative self-efficacy on employee creativity - Roshayati Abdul Hamid; Mohd Radzuan Rahid; Siti Ngayesah Ab Hamid (Penerbit Universiti Kebangsaan Malaysia, 2020)
Employees are the key determinants of an organization’s success because they possess the greatest source of the organization’s creativity. To produce a highly creative thinker, employee participation in the creative-relevant process is required. However, different forms of employee participation may benefit the organization differently. Mainly, researchers agreed on three forms of participation, namely full-autonomous or discretion over individual work tasks, semi-autonomous teamwork and consultative participation. The objective of this study is to examine the relationship between the different forms of employee participation in creative-relevant process and employee creativity. In addition, creative self-efficacy has demonstrated a relationship with creativity among employees. Underpinned by the Social Cognitive Theory, this study further examined the effect of creative self-efficacy on employee creativity and as a moderator for the relationship between creative-relevant process and employee creativity. We employed a quantitative approach by distributing questionnaires to employees who are working in public/private service sectors in Malaysia and 250 employees had responded. The study hypotheses were tested using PLS structural equation modeling. The results of the study showed that there is (a) a significant relationship between full-autonomous and consultative participation in the creative-relevant process; (b) a nonsignificant relationship between semi-autonomous and creative-relevant process; (c) a significant relationship between creative-relevant process and employee creativity; (d) a significant relationship between creative self-efficacy and employee creativity, and (e) a nonsignificant moderated relationship of creative self-efficacy. This study adds to the body of knowledge on the importance of examining the different forms of employee participation and enforcing continuous training in creative-relevant process in order to develop employee creativity.